The new technology elite : how great companies optimize both technology consumption and production - Mirchandani, Vinnie (Hoboken, New Jersey : John Wiley & Sons, 2012)
'How-to guidance for optimizing incumbent technologies to deliver a better product and gain competitive advantage. Their zip codes are far from Silicon Valley. Their SIC codes show retail, automobile or banking. But industry after industry is waking up to the opportunity of'smart' products and services for their increasingly tech-savvy customers. Traditionally technology buyers, they are learning to embed technology in their products and become technology vendors. Discussing how your company can unleash its own internal Apple and Google-type of technology wizardry, The Technology Turnaround Imperative uses examples from several industries and countries to highlight the adaptations enterprises will need to make in their unique business settings to gain competitive advantage. Contrasts the productivity that Apple, Google and others have demonstrated in the last decade to that of the average enterprise technology group Reveals how to leverage what companies have learned from Google, Apple, Amazon.com, and Facebook to your company's advantage Designed for business practitioners, CEOs, CFOs, CIOs, technology vendors, venture capitalists, IT consultants, marketing executives, and policy makers Other titles by Vinnie Mirchandani: The New Polymath: Profiles in Compound-Technology Innovations If you're looking to encourage technology innovation, look no further. The Technology Turnaround Imperative provides the building blocks your company needs to become innovative through incumbent technologies'--
Includes bibliographical references (pages 333-366) and index.
Keywords: Technological innovations -- Management; Organizational change; Industrial management